Transformation of Religious Services in Marginalized Areas: Engineering the Cluster System Policy for the Deficit of Christian Teachers and Counselors in South Sumatra - Parluhutan Lumban Batu (JURNAL ILMIAH GEMA PERENCANA, 2026)
This policy study is motivated by the low accessibility of religious services for Christians in marginalized areas of South Sumatra Province, characterized by a chronic gap in the ratio of religious instructors to religious teachers. The main problem focuses on the distribution of functional personnel, which is centralized in urban areas, while transmigration and coastal areas experience a lack of sustainable education and spiritual guidance services. This study uses a descriptive qualitative methodology with a policy evaluation approach modeled after William N. Dunn, which includes criteria for effectiveness, efficiency, adequacy, equity, responsiveness, and technical feasibility. Using the Urgency, Seriousness, and Growth (USG) scoring technique, it was found that the inequality in human resource distribution is the most pressing issue requiring immediate intervention. The analysis results indicate that conventional recruitment mechanisms fail to address the extreme geographic barriers in South Sumatra. Therefore, this study recommends policy engineering through the implementation of a "Cluster System" or Integrated Religious Service Unit. This scheme legalizes the accumulation of teacher and instructor workloads across locations within a single service zone to fulfill administrative requirements for civil servants and professional allowances. Through this regulatory transformation, it is hoped that the problem of the small number of students at one coordinate point can be overcome, so that the state can guarantee the fulfillment of citizens' constitutional rights to embrace religion and receive proper religious education without being hampered by spatial and administrative limitations.